Analysis Of Company Performace With Balance Scorecard Method (Study At PT. Telkom Indonesia Witel Lampung) - Permatasari, Dewi; Suripto, Suripto (Jurnal Kompetitif Bisnis, 2022)
The purpose of this study was to determine the performance of PT. Telkom Indonesia Witel Lampung when measured by the balanced scorecard method which looks at it from four perspectives. This type of research is descriptive research using a quantitative approach. The population in this study is PT. Telkom Indonesia Witel Lampung and the samples used are employees and consumers of PT. Telkom Indonesia Witel Lampung with a total sample of 100 respondents, of which consumers are 75 respondents while employees are 25 respondents. Data collection techniques through observation, interviews, questionnaires and documentation. The measurement results with the balance scorecard from a financial perspective are considered very good. The measurement results with the balance scorecard from the customer perspective are considered good. The measurement results with the balanced scorecard on the internal business process perspective are considered very good. The measurement results with the balanced scorecard on the growth and learning perspective are considered very good. Based on the results of the study, it was found that the results of the measurement with the performance balance scorecard of the four perspectives of PT. Telkom Indonesia Witel Lampung overall is considered very good.